Techniques in chitosan extraction from indigenous crab and utilization in bio-filtration of crude oil polluted water - Uchechi Emmanuella Nwogu; Angela Chika Udebuani; Tochukwu Nicholas Ugwu; Jude Chimezie Ajaraogu; Chidinma Yvonne Iro (Sustinere: Journal of Environment and Sustainability, 2023)
The techniques for chitosan extraction from indigenous crabs were assessed using physicochemical properties of the chitosan, and its utilization in the treatment of crude oil polluted water was investigated. Physicochemical properties, heavy metal analytic method (AAS), and hydrocarbon analysis (GC-MS method) of the water samples were employed for this investigation. Results obtained from the physical and chemical properties of the chitosan extracted from indigenous crabs (Scylla species) showed a comparable percentage yield (53% and 50%) compared to synthetic chitosan (72%). The pH values obtained from the chitosan ranged from 6.9 – 13.0, while the percentage degree of deacetylation (DDA) ranged from 60 – 75%. The water quality obtained from Ochani River, filtered with chitosan, yielded the best result with chitosan C compared to chitosan B. The heavy metal content in the polluted Ochani River was totally removed with the control (synthetic chitosan A) compared to chitosan C, which showed a comparably reduction. However, the bio-filtration with chitosan B also revealed better reduction compared to chitosan A. The study established that irrespective of the crude method applied in the extraction of the chitosan from indigenous crabs, its efficacy in treating crude oil-polluted Ochani River was highly impactful.